Sacramentality of Kishna-avatara in Bhagavata Purana - Sheridan, Daniel P (Journal of Dharma, 1984)
In the history of Bhägavatism and Vaisnavism the Bhägavata Puräpa, although a late piece of literature, gives a conclusive resolution to the problem of the personality of the Supreme Deity for all those schools of Vai9navism which regard it as authoritative. The Deity of later Bhägavatism had an inclusive quality which enabled him to absorb many local deities and cults. It did this through the doctrine of the divine manifestations (avatäras) to which is to be attributed much of Bhägavatism’s populqrity. "The syncretism effected through this doctrine," in the words of S. Jaiwal, "was sometimes manical and sometimes popular in character, but to a great extent it was the reconciliatory attitude of Vaisnavism which gave the country a kind of cultural unity and succeeded in establishing the same kind of social structure all over India. "1 The .Bhägavata Purãna played an important role in this process. Further, the character of its Deitv and his appearances, its non-dualism, and the fervour of its devotion, give the Bhãgavata its singular importance.